Recent Progress and Development of Wind Energy Potential in Malaysia: A Review - Lawan, S. M.; Abidin, W. A. W. Z.; Chai, W.Y; Baharun, A.; Masri, T. (IDOSI Publication, 2013)
With the rapid growth of fossil fuel price and subsequent consideration of exhausting non-renewable energy sources, the attention of engineers, designers and researchers has focuses in promoting pollution free energy sources. Malaysia has abundant of renewable energy sources such as hydro, solar, tidal, biomass and wind. But, for the fact that the country lies entirely in equatorial region, the annual mean wind speed ranges from 2.0m/s-8.983 m/s, respectively. This paper focuses on recent review on wind energy progress and development in Malaysia. The basic concept of wind speed distribution and spatial models applied in Malaysia is discussed. In addition, an overview on the country energy policies, wind speed variation, power and energy in wind are also presented.